Surgical Debulking Modifies Notch Signaling and May Improve Vismodegib Effectiveness for Locally Advanced Basal Cell Carcinoma - Natella Maglakelidze; Samantha L. Gettle; Amy L. Longenecker; Allison T. Vidimos; Elizabeth M. Billingsley; Ryan P. Hobbs; Charlene Lam (Elsevier, 2024)
Smoothened inhibitors, such as vismodegib, exhibit remarkable success in treating patients with locally advanced basal cell carcinoma (LaBCC). Yet, vismodegib efficacy is hindered by notable side effects, which often lead to treatment discontinuation and subsequent relapse in patients with LaBCC. Prolonged remission was previously reported in patients with LaBCCs who underwent surgical debulking before starting vismodegib. In this study, we enrolled 4 patients with LaBCC who underwent debulking followed by vismodegib therapy to assess their clinical outcomes and analyze the cutaneous molecular changes occurring as a result of surgical intervention. After LaBCC debulking, patients underwent a punch biopsy of residual basal cell carcinoma tissue 1 week later. RT-qPCR analysis of 24 Notch and Wnt signaling-associated genes revealed elevated PTCH1, HEY2, LGR6, FZD2, LEF1, ALCAM, and RUNX1 expressions in follow-up biopsies compared with those in patient-matched debulked tissue. Immunoblot and immunostaining further confirmed elevated Notch signaling in follow-up biopsy tissue compared with that in patient-matched debulked tumor tissue. Patients 1, 3, and 4 displayed a clinical response to debulking followed by vismodegib, whereas patient 2 was lost to follow-up after debulking. These findings suggest that surgical manipulation of LaBCCs is correlated with molecular alterations in signaling pathways associated with cellular reprogramming.